Chemogenetic and optogenetic stimulation of zona incerta GABAergic neurons ameliorates motor impairment in Parkinson’s disease - Fenghua Chen; Junliang Qian; Zhongkai Cao; Ang Li; Juntao Cui; Limin Shi; Junxia Xie (iScience, 2023)
Summary: Parkinson’s disease (PD) is characterized by the degeneration of dopaminergic neurons in the substantia nigra and leads to progressive motor dysfunction. While studies have focused on the basal ganglia network, recent evidence suggests neuronal systems outside the basal ganglia are also related to PD pathogenesis. The zona incerta (ZI) is a predominantly inhibitory subthalamic region for global behavioral modulation. This study investigates the role of GABAergic neurons in the ZI in a mouse model of 6-hydroxydopamine (6-OHDA)-induced PD. First, we found a decrease in GABA-positive neurons in the ZI, and then the mice used chemogenetic/optogenetic stimulation to activate or inhibit GABAergic neurons. The motor performance of PD mice was significantly improved by chemogenetic/optogenetic activation of GABAergic neurons, and repeated chemogenetic activation of ZI GABAergic neurons increased the dopamine content in the striatum. Our work identifies the role of ZI GABAergic neurons in regulating motor behaviors in 6-OHDA-lesioned PD model mice.